Atratores para processos generalizados e aplicações a um problema não autônomo com dinâmica na fronteira - Samprogna, Rodrigo Antonio (2017)
This work is dedicated to the study of the asymptotic behavior of nonautonomous evolution problems without uniqueness of solution. More specifically, to the existence of attractors, in different contexts, for dynamical systems that represent the behavior of such problems. We also consider applications for a class of p-Laplacian nonautonomous problems with dynamical boundary conditons.